Development of a Mandarin-Indonesian Pocket Dictionary in the Tire Industry Planning Sector - Chahyaningtyas, Ajeng Mutiara; Marsuki, Ria Riski; Siregar, Sheyra Silvia (Universitas Negeri Semarang, 2025)
According to some observations, many Indonesian Mandarin translators that work in Chinese companies have some difficulties in explaining and describing words of technical language especially in the tire producing industry originally in Mandarin into Indonesian or vice versa. Whereas this article aims to produce an effective pocket dictionary Mandarins-Indonesian in the planning sector of the tire industry. The development of pocketbook or pocket dictionary is done by researching words and vocabulary and developing it into a small dictionary. The results of developing a pocket dictionary in the planning section of the tire industry is easier and improves the efficiency of the translation process whilst working.